European Transport Research Review An Open Access Journal - Bekiaris, Evangelos; May, Anthony D.; Geurs, Karst
European Transport Research Review (ETRR) is a peer-reviewed open access journal publishing original high-quality scholarly research and developments in areas related to transportation science, technologies, policy and practice. Established in 2008 by the European Conference of Transport Research Institutes (ECTRI), the Journal provides researchers and practitioners around the world with an authoritative forum for the dissemination and critical discussion of new ideas and methodologies that originate in, or are of special interest to, the European transport research community. The journal is unique in its field, as it covers all modes of transport and addresses both the engineering and the social science perspective, offering a truly multidisciplinary platform for researchers, practitioners, engineers and policymakers. ETRR covers the following main areas of interest: Freight transport and logistics Transportation infrastructure Mobility and transport behavior Transportation ergonomics and human factors Transportation safety and security Transportation planning and policy Transportation economics Transportation system management, including Intelligent Transportation Systems (ITS) Environmental issues in transportation and climate change Vehicle design & technology Highway engineering, railway engineering, waterway transportation and air transport also fall into the journal’s scope. Of particular interest are topics like: transportation sustainability; accessibility and equity; technologies for improving network and vehicle efficiency; advances in integrated transport systems and intermodal transportation; traffic flow theory and modeling; IT technologies for transport data collection and analysis; innovative vehicle design; and strategies for vehicle-to-vehicle communications. The Journal encourages thematic collections of related articles from major European transport research projects, major conferences such as the TRA, ETC and WCTR, and international networks such as NECTAR. ETRR is aimed at a readership including researchers, practitioners in the design and operation of transportation systems, and policymakers at the international, national, regional and local levels. While its focus is on Europe, it will be of interest to anyone wishing to learn from European experience or to develop new applications for European practice.